Towards a holistic view of land and water management in the Gamtoos River catchment: applying a political geoecology approach - Robb, Breanne Nicola (Rhodes University, Faculty of Science, Department of Geography, 2017)
The Eastern Cape of South Africa is characterised by water scarcity, constraint on usage, and inter-basin transfers. Water from the Gamtoos River catchment supplies water users both within the catchment and outside the catchment boundaries. This requires careful management of water and land to prevent overexploitation. However, management is complex as it is divided among various stakeholders with differing interests. Political geoecology is an approach that has the potential to provide holistic insight into the catchment's water context. It was proposed to account for spatial patterns underlying interrelationships between resource distribution, human productive activity, and power relations by integrating the fields of political ecology and geoecology. This research was undertaken to further develop political geoecology as an approach for examining human-environment relations in geography through a case study of land and water management in the Gamtoos River catchment and its subcatchments. Distribution of resources and human influences were elucidated through generation of maps. To facilitate spatial analysis, the study area was delineated into catchment zones. Additionally, stakeholders were identified and classified at local, regional, national, and international levels. Power relations between stakeholders were investigated through qualitative content analysis of transcribed semi-structured interviews and survey questionnaires that were administered to 34 research participants (selected through purposive and snowball sampling) directly involved in resource management in the catchment. Findings were spatially interpreted for each of the zones. The source zone was characterised by natural vegetation, steep, rugged topography, limited access ability, and power relations around restoration and conservation interests, which arose most significantly in the Baviaanskloof. The natural recapture zone was characterised by irrigated cultivation in areas of less harsh terrain in the upstream (Baviaanskloof and Kouga) sub-catchments. In the marginal Baviaanskloof, localised power relations over water distribution primarily arose. In the thriving commercial farming context of the Kouga, power relations included a local upstream-downstream legal conflict, competing levels of governance, issues with establishing water users' associations (WUAs), and lack of adequate implementation of processes by government. Regional power relations are most prominent in the thriving commercial farming context of the overlapping regulated recapture and final use zones in the downstream Gamtoos sub-catchment. The reliance on upstream sub-catchments and tensions with the city of Port Elizabeth over water use are mediated through decisions made at the national level. Non-location specific power relations included indirect influence through energy, markets, and standards organisations, barriers in government preventing successful process implementation, and equity issues (particularly limiting the success of emerging farmers). These results illustrated that resource distribution, human productive activity, and power relations combine to produce unique characteristics in each of the zones in the Gamtoos catchment. The application of political geoecology in this case study situated the approach as useful for examining human- environment relations in geography.
Keywords: Uncatalogued